Testing ecological speciation in the Caribbean octocoral complex Antillogorgia bipinnata-kallos (Cnidaria: octocorallia) :an integrative approach (2018)
The ecological speciation is a central concept in evolution to differentiate one of the two big processes by which natural selection can produce new species. Defined as the evolution of reproductive isolation by divergent natural selection in populations adapting to different ecological environments, the ecological speciation serves as a framework to test explicit predictions on the extent of natural selection to explain the diversification patterns we observe in the living forms. The present research aimed to test a putative ecological speciation scenario for two close related species where the phenotypic divergence of colonial forms overlaps between species along the depth cline. Antillogorgia bipinnata (Verrill 1864) and A. kallos (Bielschowsky 1918), conform a group of Caribbean corals where species pairs are distributed in sympatry along broad environmental ranges. We addressed this hypothesis by an integrative approach including a reciprocal transplants experiment, finding an adaptive plasticity response between depths, high survival rates and a genetic component explaining the variance of the traits assessed. Population genomic analyses with a pooling strategy detected an association between levels of genetic differentiation and habitats in four locations, implying parallel events of genetic divergence. Additionally, observations of reproductive asynchrony provided a potential mechanism for gene flow reduction. Finally, a fine-scale population genomic analysis remarkably supports the taxonomical status of the two species. Deepening in the role of plasticity, environmental mechanisms for gene flow reduction, macro- and micro-spatial genetic structure and the functional background of divergence, this research provides substantial elements to propose an ecological speciation scenario compatible with the diversification patterns for other marine organisms where the species can arise without evident barriers for the evolution of the adaptive genetic divergence